History and Fiction: An Uneasy Marriage? - Jan Thomas Lindblad (Humaniora, 2018)
This essay discusses the relationship between history as a science and fiction as a genre of literature. It starts with a brief digression on the characteristics and pitfalls of the historical novel, including its development over time. Past experience is highlighted with the aid of a selection of acknowledged novelists making intensive use of historical information. Recent new trends are illustrated by professional historians becoming novelists. A final section offers reflections on how to combine the demands of authenticity in history with the demands of drama in literary fiction.